PENDUGAAN KOEFISIEN TANAMAN UNTUK MENGHITUNG KEBUTUHAN AIR DAN MENGATUR JADUAL TANAM KEDELAI DI LAHAN KERING LAMPUNG - Tumiar K K. Manik; R.A. Bustomi Rosadi; Agus Karyanto; Anggun Ika Pratya (JURNAL AGROTROPIKA, 2010)
One strategic agriculture commodity for Indonesia is soybean. Therefore, Indonesia should make an effort to be self sufficient in soybean production. For that purpose the planting area should be extended to dry land area. Crops water need is one important factor that needs to be considered in cultivating crops over dry land area. Calculating crops water need is necessary for irrigation schedule and plating date. Crops water need is calculated with measuring the crops evapotranspiration Crops evapotranspiration is calculated using gravimetric method or with lysimeter. Reference evapotranspiration is calculated in some different methods such as gravimetric method, using evaporimeter pan or using estimation models. Crops coeficient is calculated with dividing crops evapotranspiration with reference evapotranspiration. The purpose of this research is to calculate soybean crops coefficient in order to recommend soybean planting date in Lampung dry land. Crops evapotranspiration was calculated in gravimetric methods while reference evapotranspiration was calculated with gravimetric method, evaporimeter pan and Penman-Monteith model. The results showed that maximum crop evapotranspiration was 20 mm/week or about 3 mm/day while maximum reference evapotranspiration was 24 mm/week. Soybean crop coefficients were 0.36 in cotyledon phase (VE) to V1 phase; 0.42 on V2 phase; 0.76 on V3 phase; 0.68 on R1 phase; 1.10 on phase R3; 0.78 on R5 phase and 0.21 on R8 phase. Monts which are suitable for planting soybean are December to May. Therefore, soybean could be planted in dry land without irrigation facilities one time after paddy (December – February) or twice as long as at the first planting date the area is in good drainage condition. Key words: crops evapotranspiraton, crops coefficients, crops water need, reference evapo-transpiration, planting date